Finding coherence between EU concentrations-related instruments - Catalin Rusu (Market and Competition Law Review)
Concentrations with EU relevance, depending on their features, may fall under multiple legal regimes. EU/national merger control systems, antitrust rules, the Digital Markets Act, and the Foreign Subsidies Regulation impose (more or less) comprehensive jurisdictional, procedural and substantive requirements on such transactions. The manner in which these legal realms interact is remarkable from several standpoints: concentrations are tested ex-ante or ex-post, for various sorts of effects, using distinct methodologies and substantive tests. The merging parties may also expect that their transactions switch jurisdictions or are assessed in parallel, or subsequently, by different enforcers. The procedural roadmaps and requirements they are confronted with during the assessment processes cover broad ranges and oftentimes require skilful navigation. This contribution discusses the interplay between the merger control, antitrust, DMA and FSR regimes, attempting to assert whether addressing concentrations with EU relevance is based on coherently interacting frameworks. In doing this, the contribution weighs in on whether the EUMR continues to take centre-stage when it comes to the assessment of such concentrations – a role one could reasonably expect a mature piece of EU secondary law is apt to play.